Oral and systemic manifestations of congenital hypothyroidism in children. A case report. - Carmen Ayala; Obed Lemus; Maribel Frías (Universidad de Concepción., 2015)
Hypothyroidism is the most common thyroid disorder. It may be congenital if the thyroid gland does not develop properly. A female predominance is characteristic. Hypothyroidism is the most common congenital pediatric disease and its first signs and early symptoms can be detected with neonatal screening. Some of the oral manifestations of hypothyroidism are known to be: glossitis, micrognathia, macroglossia, macroquelia, anterior open bite, enamel hypoplasia, delayed tooth eruption, and crowding. This paper briefly describes the systemic and oral characteristics of congenital hypothyroidism in a patient being treated at a dental practice. The patient had early childhood caries and delayed tooth eruption. There are no cases of craniosynostosis related to the primary pathology, which if left untreated, increases the cranial defect. Early diagnosis reduces the clinical manifestations of the disease. Delayed tooth eruption will become a growing problem if the patient does not receive timely treatment and monitoring.